Attitudes and work preferences toward older people among Malay undergraduate nursing students - Sharifah Munirah Syed Elias; Nor Faeziah Jaafar; Lee Siew Pien (Makara Journal of Health Research, 2020)
Background: The aging population is increasing globally and requires a high demand for healthcare services in several countries. As a way of preparing future nurses in aged care, substantial incorporation of gerontology courses in the nursing program to meet future needs is required. The present study aimed to investigate the association between attitudes and work preferences toward older people among undergraduate nursing students.